Cyriax's deep friction massage application parameters: Evidence from a cross-sectional study with physiotherapists. (December 2017) - Chaves, Paula; Simões, Daniela; Paço, Maria; Pinho, Francisco; Duarte, José Alberto; Ribeiro, Fernando
Abstract: Background: Deep friction massage is one of several physiotherapy interventions suggested for the management of tendinopathy. Objectives: To determine the prevalence of deep friction massage use in clinical practice, to characterize the application parameters used by physiotherapists, and to identify empirical model-based patterns of deep friction massage application in degenerative tendinopathy. Design: observational, analytical, cross-sectional and national web-based survey. Methods: 478 physiotherapists were selected through snow-ball sampling method. The participants completed an online questionnaire about personal and professional characteristics as well as specific questions regarding the use of deep friction massage. Characterization of deep friction massage parameters used by physiotherapists were presented as counts and proportions. Latent class analysis was used to identify the empirical model-based patterns. Crude and adjusted odds ratios and 95% confidence intervals were computed. Results: The use of deep friction massage was reported by 88.1% of the participants; tendinopathy was the clinical condition where it was most frequently used (84.9%) and, from these, 55.9% reported its use in degenerative tendinopathy. The "duration of application" parameters in chronic phase and "frequency of application" in acute and chronic phases are those that diverge most from those recommended by the author of deep friction massage. Conclusion: We found a high prevalence of deep friction massage use, namely in degenerative tendinopathy. Our results have shown that the application parameters are heterogeneous and diverse. This is reflected by the identification of two application patterns, although none is in complete agreement with Cyriax's description. Highlights: DFM is highly used by Portuguese physiotherapist in the treatment of tendinopathy. We found a high heterogeneity and variability in the application parameters of DFM. Two patterns of DFM application were identified.